MON-434 Familial Alactogenesis Associated with a Prolactin Mutation - Moriwaki, Mika (J Endocr Soc, 2019)
BACKGROUND: Isolated prolactin deficiency is a rare disorder manifesting as absence of puerperal lactation. We identified a family with multiple members who had alactogenesis and examined genetic causes. SUBJECTS: Three women in one family (proband, sister and niece) reported puerperal alactogenesis, i.e. no milk production postpartum. All the women had regular menstrual cycles during their reproductive years. The proband, currently 66 yrs, had 7 pregnancies and 2 live births. Prolactin level was 1.16 ng/mL (2.8-29.2 ng/mL) at the age of 47 yrs. The sister, currently 73 yrs, had 3 children. Her prolactin level was 1.4 ng/mL (2.8-29.2 ng/mL) at the age of 64 yrs. Both women had menopause before age 45 years. The niece, currently 43 years old, had infertility of unknown cause and conceived 2 children with fertility treatment. She had prolactin levels of 1.13 ng/mL, 0.618 ng/mL and 0.759 ng/mL at the age of 34-36 yrs. METHODS: DNA and mRNA were extracted from blood of all three women and a fertile control with a history of normal lactation. PRL exons 1-6 were Sanger sequenced from the DNA. cDNA was subjected to RT-PCR with primers spanning intron 5 and the terminal portion of exon 6. RT-PCR was analyzed using the 2(-ΔΔC)T method. Prolactin mRNA expression was compared among the affected women and the control subject. RESULTS: We identified a heterozygous mutation (c.658C>T) changing CGA (arginine) to TGA (stop codon) (p.Arg220Ter) in exon 6 of the prolactin gene. PRL mRNA expression (0.011±0.003 vs. 1.0±0.0; p<0.001) and terminal exon 6 expression (0.0027±0.0028 vs. 0.99±0.05; p<0.001) was decreased compared to control mRNA expression. DISCUSSION: We have identified a genetic cause of puerperal alactogenesis resulting from a stop-gain mutation in the prolactin gene (PRL). PRL mRNA expression is decreased in these subjects. These findings suggest that the mutated PRL may undergo nonsense decay. The low circulating prolactin resulted in inability to breastfeed. It may also be the cause of infertility and early menopause, but further studies are needed. CONCLUSION: We report a stop-gain mutation in exon 6 of the prolactin gene (PRL) resulting in familial puerperal alactogenesis.